Brazilian social security reform and the need to respect legal certainty and predictability (Revista do Tribunal Regional Federal da 3ª Região, 2017)
More than six hundred years ago, René Descartes said "cogito, ergo sum". Inspired by the rationalism he inaugurated, in these turbulent times that Brazil is going through, in which so many arguments, some correct, others pure bait, are being produced to justify the reform of Social Security, I examined the recent Constitutional Amendment bill presented by the federal government, which is already being processed in the National Congress. Before dealing with some of the points of the bill, the premise on which the whole discourse is based and the government's own policy of the need for reform is not so clear, despite the speeches, advertisements and newspaper reports. It's not new to hear about the detour of Social Security funds for purposes that have nothing to do with it. Although Article 194 of the 1988 Constitution created a Social Security system (Welfare, Assistance and Health), establishing the hypotheses for collecting contributions from productive entities to meet these needs, the truth is that the funds collected have never been used solely for Social Security.If there is no certainty about the statistics, another point that makes the need for a pension reform like the one proposed by the federal government quite debatable is the fact that the country is currently going through a serious recession, perhaps the worst in its history, in which the most protected political and economic groups in society simply want to transfer spending, literally passing on "the bill" to the weakest sectors of society. This is, in fact, a political war and the Social Security reform is one of the battles in which the economic elite wants nothing to lose in order to help the country recover. It is important to note that since 1988, the country has adopted a system of social security solidarity, and this has been recognized by the Supreme Court. A capitalization system could have been chosen, I even think it would have been a better option. However, it was not chosen. It turns out that there are countless forms of fraud, and I don't intend to cite papers and other documents in this brief study, but it is not difficult to see that a large part of the benefits paid out today in Brazil are fraudulent, making Social Security and Brazilians victims of the crime in article 171, § 3, of the Penal Code (embezzlement). Furthermore, tax evasion is very high in the country, in addition to the countless forms of waivers, remissions, pardons, installments and refinancing. And what can we say about so-called "tax planning", the difference between which and tax fraud is quite blurred, with the result that individuals with high economic power and liable to be charged high amounts for Social Security often get away with it, paying derisory rates compared to individuals in general, many of whom are taxed at 27.5% of income tax.
Keywords: Social security×reform×legal certainty×predictability×; social security; reform; legal certainty; predictability